Fixed Point and Weak Convergence Theorems for (α,β)-Hybrid Mappings in Banach Spaces - Tian-Yuan Kuo; Jyh-Chung Jeng; Young-Ye Huang; Chung-Chien Hong (Abstract and Applied Analysis)
We introduce the class of (α,β)-hybrid mappings relative to a Bregman distance Df in a Banach space, and then we study the fixed point and weak convergence problem for such mappings.